Standardizing the freeze‐thaw preparation of growth factors from platelet lysate. Issue 4 (9th February 2017) - Strandberg, Gabriel; Sellberg, Felix; Sommar, Pehr; Ronaghi, Martin; Lubenow, Norbert; Knutson, Folke; Berglund, David
Abstract : BACKGROUND: Over the past decades, the focus on the regenerative properties of platelets (PLTs) has intensified and many PLT‐derived growth factors are readily used in medical settings. A general lack of standardization in the preparation of these growth factors remains, however, and this study therefore examines the dynamics of growth factors throughout the freeze‐thaw procedure. STUDY DESIGN AND METHODS: Plateletpheresis (PA) and PLT‐poor plasma (PPP) samples were collected from 10 healthy donors. PA was lysed to produce PLT lysate (PL) for 1, 3, 5, 10, and 30 freeze‐thaw cycles. The resulting growth factor and cytokine concentrations from PPP, PA, and PL of different cycles were analyzed and compared using enzyme‐linked immunosorbent assay and multiplex bead assays. RESULTS: PL produced by the freeze‐thaw procedure resulted in approximately four‐ to 10‐fold enrichment of transforming growth factor‐β1, epidermal growth factor, PLT‐derived growth factor (PDGF)‐AB/BB, PLT factor‐4, and fibroblast growth factor‐2. The increase in concentrations plateaued at Cycles 3 and 5 and in some cases declined with further cycles. The concentrations of insulin‐like growth factor‐1, hepatocyte growth factor, vascular endothelial growth factor, and bone morphogenetic protein‐2 in PL were essentially comparable to those in PPP. CONCLUSION: Using the freeze‐thaw method, optimal preparation of PL with regard to the concentration of growth factors was achieved at Cycles 3 to 5. Based on our findings, the clinical significance of using a greater number of cycles is likely limited.